2012
DOI: 10.1002/mame.201200034
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Nucleating Agents for Poly(butylene terephthalate) Based on 1,3,5‐Benzenetrisamides

Abstract: 1,3,5‐Benzenetrisamide‐based supramolecular nucleating agents for poly(butylene terephthalate) (PBT) are reported. 1,3,5‐Benzenetrisamides combine excellent thermal stability with chemical resistance, basic requirements for the use in high‐melting thermoplastics. To establish structure–property relationships, the central core and peripheral substituents are varied systematically. Dissolution and crystallization behavior of the additives in the PBT melt and the crystallization temperature of PBT are investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…Such intriguing modifications of the supramolecular polymer properties upon subtle changes in the close environment of the hydrogen-bonded assembling units has also been observed for benzene-1,3,5-tricarboxamides (BTAs). 39 BTAs are ubiquitous synthons in supramolecular chemistry due to their structural simplicity, the predictable mode of association of the monomers into rod-like structures and important applications as gels, [40][41][42][43][44][45] liquid-crystalline materials, 21,40,41,[46][47][48][49][50][51][52][53] thin films with remnant polarization, 54 additives for polymers, [55][56][57][58] MRI agents, [59][60][61][62] chiral templates for Au NPs 63 and catalysts. [25][26][27][28][29] Meijer and colleagues have shown that the stability of the rod-like aggregates (or stacks) formed by BTAs bearing chiral methyl-alkyl side chains increases when the stereogenic center is closer to the amide functions.…”
Section: Introductionmentioning
confidence: 99%
“…Such intriguing modifications of the supramolecular polymer properties upon subtle changes in the close environment of the hydrogen-bonded assembling units has also been observed for benzene-1,3,5-tricarboxamides (BTAs). 39 BTAs are ubiquitous synthons in supramolecular chemistry due to their structural simplicity, the predictable mode of association of the monomers into rod-like structures and important applications as gels, [40][41][42][43][44][45] liquid-crystalline materials, 21,40,41,[46][47][48][49][50][51][52][53] thin films with remnant polarization, 54 additives for polymers, [55][56][57][58] MRI agents, [59][60][61][62] chiral templates for Au NPs 63 and catalysts. [25][26][27][28][29] Meijer and colleagues have shown that the stability of the rod-like aggregates (or stacks) formed by BTAs bearing chiral methyl-alkyl side chains increases when the stereogenic center is closer to the amide functions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently this class of supramolecular building blocks was reviewed by Palmans et al 1,3,5‐Benzenetrisamides are accessible with a few synthetic steps and their structure can be tailored for a broad range of applications including nanotechnology, polymer additives, and biomaterials. Benzenetrisamides can be applied, for example, as nucleating agents for poly(vinylidene fluoride), poly(butylene terephthalate) (PBT), poly(ethylene‐ co ‐propylene), polylactides, and isotactic poly(propylene) ( i ‐PP) . In some cases trisamides are also efficient clarifiers .…”
Section: Resultsmentioning
confidence: 99%
“…The physical and chemical properties of semi-crystalline polymers depend on their crystal structure and spherulite size to a large extent, both of which can be controlled by the addition of a nucleating agent into the polymer [4]. Isotactic polypropylene (iPP) is one of the most important thermoplastics with multifunctional characteristics [5].…”
Section: Introductionmentioning
confidence: 99%